Feminist Care and Being Tough Enough: An Interview with Michelle Forrest - Downey, Adrian; McKinstry, Renée (Philosophical Inquiry in Education, 2025)
This article takes the form of an interview with Dr. Michelle Forrest. A philosopher of education, a teacher, a feminist, and a mentor to many, Michelle has been a longtime member of the Canadian philosophy of education community. This interview, conducted by her colleague, Adrian Downey, and her PhD student, Renée McKinstry, looks back over Michelle’s work in philosophy of education, offering her the chance to reflect on her contributions considering the changes in educational thinking and social circumstance throughout her career. Specifically, Michelle discusses her dissertation on pedagogical openness and the openness of the text, the feminist ethics of care and feminist irony, the dangers of comparative thinking, coloniality, and the significance of the Canadian Philosophy of Education Society (CPES) to her career and life as a philosopher of education. The interview concludes with Michelle’s advice to future scholars working the foundations of education and especially philosophy of education.